DEWAN KOMISARIS INDEPENDEN DAN KEPEMILIKAN MANAJERIAL TERHADAP KINERJA KEUANGAN - Putri Azizah; Aminar Sutra Dewi (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2023)
The financial performance of a company can be interpreted as a measure of the performance of a company that shows good conditions over a certain period of time. The purpose of measuring financial performance is to obtain useful information about cash flow, use of funds, efficiency and effectiveness. This study aims to determine and analyze the effect of independent board of commissioners and managerial ownership on financial performance in manufacturing companies. The data processed is secondary data from the annual reports of 20 manufacturing companies listed on the IDX for 2017-2021 taken through purposive sampling. The method used in this study is the panel data regression analysis method using Eviews version 10. The results of this study indicate that the independent board of commissioners has no and significant effect on financial performance, managerial ownership has a negative and significant effect on financial performance.